Improving the organization of the enterprise's logistics system - Song, Zhiqiang (Харківський національний автомобільно-дорожній університет, 2025)
The relevance of the topic of the qualification work lies in the fact that a clearly structured logistics system is a key element of the effective functioning of enterprises in various industries in the modern economy. The work analyzes the theoretical foundations for assessing the effectiveness of an organization's logistics system; analyzes the economic activity and effectiveness of the logistics system of LLC «VIZIT-TRANS»; based on the assessment, recommendations for improving the logistics system of LLC «VIZITTRANS» are developed; the economic effect of the recommendations is demonstrated. The practical significance of this work is expressed in the recommendations developed by the author for improving the logistics system of LLC «VIZITTRANS».
Keywords: logistics system; management; logistics; transportation; evaluation methods